Clinical study on sequential treatment of severe diarrhea irritable bowel syndrome with precision probiotic strains transplantation capsules, fecal microbiota transplantation capsules and live combined bacillus subtilis and enterococcus faecium capsules - Lv, Linling; Ruan, Guangcong; Ping, Yi; Cheng, Yi; Tian, Yuting; Xiao, Zhifeng; Zhao, Xuefei; Chen, Dongfeng; Wei, Yanling (Frontiers in Cellular and Infection Microbiology, 2022)
Objective To study the effect of precision probiotic strains transplantation capsules on diarrhea irritable bowel syndrome compared with fecal microbiota transplantation capsules and live combined bacillus subtilis and enterococcus faecium capsules. Methods Two patients with severe irritable bowel syndrome were treated with precision probiotic strains transplantation capsules, fecal microbiota transplantation capsules and live combined bacillus subtilis and enterococcus faecium capsules in sequence. IBS-SSS, IBS-QoL, GSRS, stool frequency, stool character, degree of abdominal pain, GAD-7, and PHQ9 scores of patients at 0, 2, 4, 6, 8, 10, and 12 weeks of treatment were monitored and recorded, and stool samples were collected for metagenomics and metabolomics. Results It was found that the IBS-SSS score of patient case 1 decreased by 175 points and that of patient case 2 decreased by 100 points after treatment of precision probiotic strains transplantation capsules. There was no significant decrease after fecal microbiota transplantation capsules and live combined bacillus subtilis and enterococcus faecium capsules were used. At the same time, compared with fecal microbiota transplantation and live combined bacillus subtilis and enterococcus faecium capsules, the IBS QoL, stool frequency, stool character, degree of abdominal pain and GAD-7 score of patient case 1 improved more significantly by the precision probiotic strains transplantation capsules. And the stool frequency and stool character score of patient case 2 decreased more significantly. Intestinal microbiota also improved more significantly after the precise capsule transplantation treatment. And we found Eubacterium_ Eligens showed the same change trend in the treatment of two patients, which may play a role in the treatment. Conclusion precision probiotic strains transplantation capsules is more beneficial to improve the intestinal microbiota of patients than microbiota transplantation capsule and live combined bacillus subtilis and enterococcus faecium capsules, so as to better alleviate clinical symptoms. This study provides a more perfect and convenient therapeutic drugs for the treatment of IBS.